Research on the effects of digital inclusive finance on the efficiency of financial resource allocation - Fan, Yaojun; Chen, Sze Ting (Frontiers in Environmental Science, 2022)
With the rapid progress of digital technology, finance has also embarked on the fast lane of its development. Whether and how the development of digital inclusive finance can improve the efficiency of financial resource allocation have both been significant questions for the Chinese government to answer. This paper adopted the super-efficiency DEA method to measure the allocation efficiency of regional financial resources in China, integrating with the Digital Inclusive Finance (DIF) index published by the Digital Finance Research Center of Peking University, to study the influences of DIF on the Financial Resource Allocation Efficiency (FRAE). After considering the spatial factors, we found that the development of DIF could significantly promote the FRAE mainly in three aspects of coverage, depth and credit. Meanwhile, in the analysis of its mechanisms, we also discovered that DIF could promote the FRAE through human capitals and enterprise innovations. Finally, this paper indicated that the differences in regions and overcapacity levels would also modify the influences of DIF on the FRAE. The enlightenment from this paper is that relevant government departments should actively promote the development of digital inclusive finance, thereby not only improving the efficiency of financial resource allocation and the coordinated action between regions, but also promoting the transformation and upgrade of economic development methods.